Potensi Wisata Sawah Bawuoh Dan Lubuk Larangan Di Desa Talawi Hilir - Lisa Putriani; Shaufi Wardana; Ahmad Syauqi Alfathany; Betran Esa Ramadan; Fitri Aini; Melany Hapiza Warfi Simamora (Jurnal Imiah Pengabdian Pada Masyarakat (JIPM), 2025)
The development of nature-based and cultural tourism plays a crucial role in improving community welfare and preserving the environment. Talawi Hilir Village, located in Sawahlunto City, has two main tourism potentials: Sawah Bawuoh and Lubuk Larangan. Sawah Bawuoh offers a vast agricultural landscape with potential development as an agro-tourism destination. Meanwhile, Lubuk Larangan is a conservation-based ecotourism site aimed at protecting aquatic ecosystems while providing economic benefits to the local community. However, tourism development in this village faces several challenges, including lack of promotion, infrastructure limitations, low community involvement in tourism management, and threats to environmental and cultural sustainability. This study employs a qualitative research method with a literature review approach to analyze tourism potential, challenges, and development strategies. The findings indicate that improving digital promotion, enhancing infrastructure, empowering local communities, and implementing environmental regulations and cultural preservation measures are key strategies for optimizing tourism management in Talawi Hilir Village. With proper strategies and active involvement from the government, community, and private sector, tourism in this village can develop sustainably, providing long-term benefits for the local economy and environmental conservation.